Effectiveness of antimicrobial agent combinations against carbapenem-producing Klebsiella pneumoniae with KPC variants in China - Liu, Congcong; Wu, Yuchen; Zhang, Yanyan; Yan, Zelin; Gu, Danxia; Zhou, Hongwei; Dong, Ning; Cai, Chang; Chen, Gongxiang; Zhang, Rong (Frontiers in Microbiology, 2025)
PurposeCarbapenem-resistant Klebsiella pneumoniae (CRKP) producing carbapenemases poses a global threat to public health. Antimicrobial agent combinations have been promoted as a potential therapeutic strategy for infections. The most effective antimicrobial combinations against CRKP strains producing different carbapenemases are currently unclear, particularly those producing the KPC variant carbapenemases. This study is aimed to evaluate the effectiveness of various antimicrobial agent combinations against CRKP strains with different carbapenemases.MethodsA checkerboard assay involving 24 antimicrobial agent combinations was conducted on 44 strains of carbapenemase-producing CRKP isolated from patients of which 13 CRKP strains carried single KPC variants. The 24 antimicrobial combinations were based on meropenem, polymyxin, tigecycline, ceftazidime/avibactam, respectively. The fractional inhibitory concentration (FIC) indexes were calculated for each combination of antimicrobial agents.ResultsThe distribution of carbapenemases in 44 CRKP strains was as follows: KPC variants (n = 13, 29.5%), KPC-2 (n = 10, 22.7%), metallo-β-lactamases (n = 9, 20.5%), OXA-48-like (n = 12, 27.3%). In the checkerboard assay, the combination of polymyxin and aztreonam exhibited the highest synergistic effect against CRKP strains, with a rate of 95.5% (42/44). This was followed by polymyxin-meropenem at 88.6% (39/44) and polymyxin-levofloxacin at 68.2% (30/44). Additionally, polymyxin-aztreonam combination and polymyxin-meropenem showed the highest sum of synergistic and additive rates of 100.0% against KPC variant-producing CRKP strains. Notably, ceftazidime/avibactam-based combinations exhibited better synergistic effects on KPC variant-producing CRKP strains compared to other CRKP strains with adjusted p value <0.05.ConclusionOur study suggests that the combinations of antimicrobial agent could serve as potential treatment strategies against CRKP infections. Furthermore, the effectiveness of these combinations is influenced by the types of carbapenemases present. Ceftazidime/avibactam-based combinations have showed superior synergistic effects on KPC variant-producing CRKP strains.